Behaviour of primary catalysts in the biomass steam gasification in a fountain confined spouted bed. (1st October 2019) - Cortazar, M.; Lopez, G.; Alvarez, J.; Amutio, M.; Bilbao, J.; Olazar, M.
Graphical abstract: Highlights: The fountain confined conical spouted bed enhances the performance of primary catalysts. Dolomite and γ-alumina improved syngas composition and reduced tar content. Olivine and FCC catalysts reduced tar content, but hardly affect syngas composition. The lowest tar content (5.0 g Nm −3 ) was obtained using dolomite as catalyst. Light PAHs were the prevailing tar compounds on all the catalysts studied. Abstract: The performances of the primary catalysts olivine, dolomite, γ-alumina and FCC spent catalyst were evaluated in the continuous steam gasification of sawdust in a bench-scale plant equipped with a fountain confined conical spouted bed reactor. The experiments were carried out at 850 °C, and the efficiency of the gasification process was defined by gas yield, H2 production, tar concentration and composition, and carbon conversion efficiency. The benefits of the fountain confiner not only helped to improve the gas-solid contact, and therefore favoured the primary catalysts' reforming and cracking activity, but also enhanced H2 production and reduce tar formation. Thus, dolomite and γ-alumina recorded the lowest values of tar, 5.0 and 6.7 g Nm −3, respectively, which corresponded to 79% and 72% tar reduction compared to the inert sand, whereas olivine and the FCC spent catalyst recorded higher tar contents, 20.6 and 16.2 g Nm −3, respectively. It is noteworthy that light PAHs were the most abundant species in the tar (60 wt% of the whole tar content).